The RECG1 DNA Translocase Is a Key Factor in Recombination Surveillance, Repair, and Segregation of the Mitochondrial DNA in Arabidopsis. Issue 10 (13th October 2015) - Wallet, Clémentine; Le Ret, Monique; Bergdoll, Marc; Bichara, Marc; Dietrich, André; Gualberto, José M.
Abstract : Arabidopsis RECG1 acts in mtDNA repair in the suppression of ectopic recombination and in the segregation of alternative mitotypes. Abstract: The mitochondria of flowering plants have considerably larger and more complex genomes than the mitochondria of animals or fungi, mostly due to recombination activities that modulate their genomic structures. These activities most probably participate in the repair of mitochondrial DNA (mtDNA ) lesions by recombination-dependent processes. Rare ectopic recombination across short repeats generates new genomic configurations that contribute to mtDNA heteroplasmy, which drives rapid evolution of the sequence organization of plant mtDNAs . We found that Arabidopsis thaliana RECG1, an ortholog of the bacterial RecG translocase, is an organellar protein with multiple roles in mtDNA maintenance. RECG1 targets to mitochondria and plastids and can complement a bacterial recG mutant that shows defects in repair and replication control. Characterization of Arabidopsis recG1 mutants showed that RECG1 is required for recombination-dependent repair and for suppression of ectopic recombination in mitochondria, most likely because of its role in recovery of stalled replication forks. The analysis of alternative mitotypes present in a recG1 line and of their segregation following backcross allowed us to build a model to explain how a new stable mtDNA configuration, compatible with normal plant development, can be generated by stoichiometric shift.